The Rajputana Desert - Chaturvedi, M. D. (Indian Forester, 1952)
The diversion of the drainage of the Gangetic Plain from the Arabian Sea towards the Bay of Bengal brought about by earth movements which folded up the Siwaliks coupled with the sands left in the wake of the recession of what was during geological times an extension of the Gulf of Cutch have given rise to the vast stretch of the inhospitable and arid tract known as the Rajputana desert, covering an area of about 80,000 square miles. In the saline alluvial marshes of the Runn of Cutch, to the south-west of the desert, we have an illustration par excellence of the desert in the making by the desertion of the sea; the process having been accelerated by the deposition of the silt brought down by the Hakra, now extinct, and the Luni. Strong winds, which develop in this region during the summer and gather great mornentum during the monsoon months, transport, vast quantities of salt and sand to the Rajputana desert whipping it up into terrific dust storms, the fury of which is felt throughout the northwestern India. The desert has spread through the ages causing the ’westering’ of the Indus and the ’northering’ of the Sutlej, meeting an obstruction of sorts only along its eastern confines in the Aravallis and their extension up to the Delhi Ridge.